Analyzing the Resource Curse Hypothesis in Oman: The role of Financial Development and Natural Resource through ARDL method - Al Balushi, Issa; Yusoff, Nora Yusma Binti Mohamed (International Journal of Energy Economics and Policy, 2025)
This study explores the Resource Curse Hypothesis in Oman from 1990 to 2021, tackling an important question in development economics: does an abundance of natural resources impede or promote economic growth? The study also explores how financial development, trade, and urbanization influence economic performance. The analysis, using various unit root tests, confirmed that the variables are stationary, which provides a solid foundation for further modeling. The Autoregressive Distributed Lag (ARDL) bounds testing method showed a long-term cointegration relationship between the variables. The findings show that having abundant natural resources significantly boosts economic growth, thereby effectively denying the Resource Curse Hypothesis in Oman’s case. Additionally, it was observed that financial development, trade, and urbanization play important roles in fostering economic growth. To strengthen the findings, various estimation techniques were used, such as Fully Modified OLS (FMOLS), Dynamic OLS (DOLS), and Canonical Cointegration Regression (CCR), all of which supported the results of the ARDL model. The results highlight the significance of utilizing natural resources and supporting factors to promote sustainable economic growth in resource-abundant countries such as Oman.